Perancangan Dashboard Perbaikan Peti Kemas pada PT. X - Jane Oktaviani; Felecia Felecia (Jurnal Titra, 2022)
The X Corporation is a shipping logistic company established in 1984 and headquartered in Surabaya. Based on X Corporation's business model, containers are inspected and repaired first after used by customers. Thus, shipping container repaired work data are recorded and used for our study. MTBF (Mean Time Between Failure) and other important parameters that indicate the shipping containers' performance and reliability are post-processed and analyzed in this study using data mining method. The post-processed data are visualized using dashboard to make it easier to monitored in a glance. In short, the data visualization dashboard (in this study) depicts the post-processed data of damaged containers, repair works, MTBF value, types of damage, location of damage, types of repair, supplies of the component, and other parameters. Therefore, the dashboard is expected to help the companies in making decisions to improve container reliability based on MTBF values and other data that affect container reliability.